PENINGKATAN HASIL BELAJAR IPAS MATERI TUMBUHAN SUMBER KEHIDUPAN DI BUMI KELAS IV MENGGUNAKAN MODEL PEMBELAJARAN PROJECT BASED LEARNING DENGAN PENDEKATAN TaRL (TEACHING AT THE RIGHT LEVEL) DI SDN 13 PALEMBANG - Furi Ayu Novia Utami; Hesti Febriana; Fia Sisi Abriati (STKIP Subang, 2024)
The purpose of this study was to determine the improvement of student learning outcomes in the material of plant sources of life on earth in class IV by using the Project Learning model and the TaRL approach at SDN 13 Palembang. This research method is a Classroom Action Research (PTK) conducted in Class IV A, IV B, and IV C of SD Negeri 13 Palembang. This research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The learning model applied was Project Based Learning (PjBL) with the Teaching at the Right Level (TaRL) approach. The study results showed an increase after implementing the pre-cycle, cycle I, and cycle II with 93.33% of Class IV A students, 90% of Class IV B students, and 86.67% of Class IV C students reaching the KKM. Thus, there is an increase in IPAS learning outcomes on the material of plant sources of life on earth in class IV using the Project Based Learning learning model with the TaRL (Teaching at the Right Level) approach at SDN 13 Palembang.